Domestic labour, foreign capital and welfare - Broll, Udo; Hansen-Averlant, Sabine; Marjit, Sugata (Economics and Business Review, 2008)
A competitive allocation of labour across different sectors of a small open economy may not be socially optimal when one sector uses foreign specific capital. We argue that a suitably designed economic policy is required to maximize national welfare of the host country. In particular such a policy design has to take into account repatriation of factor income by multinational firms. (original abstract)